2020
DOI: 10.3390/ijms21186464
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 and NF-kB Mediated Control of Innate Inflammatory Responses in a Canine Macrophage Cell Line

Abstract: The pathogenesis of many inflammatory diseases is associated with the uncontrolled activation of nuclear factor kappa B (NF-κB) in macrophages. Previous studies have shown that in various cell types, heat shock protein 70 (Hsp70) plays a crucial role in controlling NF-κB activity. So far, little is known about the role of Hsp70 in canine inflammatory processes. In this study we investigated the potential anti-inflammatory effects of Hsp70 in canine macrophages as well as the mechanisms underlying these effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…NF-κB has been reported to play a central role in the antioxidant and anti-inflammatory responses, and also is considered as a critical transcription factor required for the expression of many cytokines [ 22 ]. Therefore, the expression of NF-κB was examined by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB has been reported to play a central role in the antioxidant and anti-inflammatory responses, and also is considered as a critical transcription factor required for the expression of many cytokines [ 22 ]. Therefore, the expression of NF-κB was examined by western blot assay.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, TLR‐mediated autophagy is reported to promote immune responses via increasing antigen processing and presentation in antigen‐presenting cells (Chou et al, 2020). Lyu et al (2020) research has shown that the upregulation of HSP70 plays a critical role in modulating LPS‐induced NF‐κB activation and cytokine expression. The increase of HSP70 in muscle and spinal cord, which may activate TLR4 in spinal cord microglia with consequent activation of an intracellular signaling cascade mediated by MyD88, resulting in NF‐қB activation and the production of proinflammatory cytokines, such as TNF‐α and IL‐6 (Dos Santos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ARF6 interacts with Rab proteins to regulate phagolysosome formation by regulating GTPase activity in P. vannamei gills cells. In hepatopancreas tissue, ARF6 plays a role in immunity of V. anguillarum infection by interacting with cytohesin.Recently, TLR-mediated autophagy is reported to promote immune responses via increasing antigen processing and presentation in antigen-presenting cells(Chou et al, 2020) Lyu et al (2020). research has shown that the upregulation of HSP70 plays a critical role in modulating LPS-induced NF-κB activation and cytokine expression.…”
mentioning
confidence: 99%
“…HSPs can prevent or arrest inflammatory damage, in which they enhance the production of anti-inflammatory cytokines (Borges et al 2012). The anti-inflammatory effect of HSP may be due to their inhibitory action of signaling pathways NF-κB and NF-κB/nuclear factor kappa B (IκB), possibly through the prevention of IκB kinase activation that stabilizes IkB (Janus et al 2011;Lyu et al 2020). Induced Hsp70 inhibited the production of pro-inflammatory cytokines, such as TNFα, IL1β, and IL6 in vitro (Wang et al 2017).…”
Section: Transcriptomic Profile Changes During Oxidative Stressmentioning
confidence: 99%